A polar surface eddy obscured by thermal stratification - Porter, M; Henley, SF; Orkney, A; Bouman, HA; Hwang, B; Dumont, E; Venables, EJ; Cottier, F (American Geophysical Union, 2020)
Mesoscale and submesoscale eddies play an important role in the distribution of heat and biogeochemical properties throughout the global oceans. Such eddies are important in the Arctic Ocean, particularly in the frontal regions, but are difficult to detect using traditional satellite‐based methods. Here we use high‐resolution in situ data from an underwater glider to identify a surface eddy that was masked from remote‐sensing observations. We hypothesize that this masking was driven by thermal stratification driven by surface heat fluxes. The eddy was likely generated north of the Polar Front, before crossing the front and traveling south. We estimate that the observed eddy contained 4 × 1010 m3 of Arctic Water. The observation of this eddy, masked in satellite observations of sea surface temperature, suggests a historical underestimation of the prevalence and importance of eddies in this key mixing region. The water column of the Barents Sea, one of the circumpolar Arctic seas has a seemingly simple structure. In the south, warm Atlantic Water dominates; in the north, cold Arctic Water dominates; while at their boundary, the Arctic Water overlies the Atlantic Water. In the summer, the Arctic Water is largely devoid of the nutrients required to fuel the growth of phytoplankton, which is key to maintaining life in the ocean. In contrast, the Atlantic Water is one of the primary sources of nutrient‐rich water into the Arctic. In this study, we have used an underwater robotic instrument to identify a patch of Arctic Water which has been shed from the Arctic sector of the Barents Sea into the Atlantic sector. This patch of water is seen to have lower phytoplankton concentrations than the surrounding water. Due to atmospheric heating of the surface, this patch would be indistinguishable from the surrounding Atlantic Water and so would be absent for satellite observations of sea surface temperature. We suggest that this temperature masking has meant that we have previously underestimated how much water is moved within these patches in the Arctic seas.